Photoelectric memory in 6H-SiC - Duisenbaev, M. (Functional Materials, 2004)
In the investigated structures, the phenomenon of photoelectric memory is observed connected with the increase of a dark current by about 3 decimal orders and retained for a long time after the structure illumination with light of E = 3 eV energy at T = 300 K. The current-voltage characteristic is I ~ Vn, where n = 4.3. Optical and temperature quenching of photoconductivity were observed. Within a narrow range of light intensity, the lux-current characteristic shows a superlinear dependence with к = 4 then passing into a sublinear one with к = 0.7. The observable maximum relaxation time of residual conductivity is т = 5-104 s. Under illumination with light of energy E = 1.1 to 2 eV, the structure exhibits a sharp reduction of т. As the voltage applied to the structure increases, т decreases. В исследованных структурах наблюдается явление фотоэлектрической памяти, связанное с возрастанием темнового тока на 3 порядка и сохраняющееся в течение длительного времени после освещения структуры светом с энергией Е = 3 эВ при Т = 300°K. Вольт-амперная характеристика I ~ Vа, где n = 4.3. Наблюдались оптическое и температурное гашение фотопроводимости. В узкой области изменения интенсивности света на люкс-амперной характеристике имеется суперлинейная зависимость с показателем к = 4, а затем переходящей в сублинейный участок с к = 0.7. Максимально наблюдаемое время релаксации остаточной проводимости т = 5-104 с. Освещение структуры светом с энергией Е = 1.1-2 эВ приводит к резкому уменьшению т. С увеличением приложенного напряжения к структуре т уменьшается. У досліджєних структурах спостерігається явище фотоелектричної пам’яті пов’язане зі зростанням темнового струму на 3 порядки, яке зберігається протягом тривалого часу після освітлення структури світлом з енергією E = 3 еВ при T = 300 К. Вольт-ам-перна характеристика I ~ Vі, де n = 4.3. Спостерігалося оптичне й температурне гасіння фотопровідності. У вузькій області зміни інтенсивності світла на люкс-амперній характеристиці має місце суперлінійна залежність з показником к = 4, яка потім переходить у сублінійну дільницю з к = 0.7. Максимальний спостережений час релаксації залишкової провідності т = 5-104 с. Освітлення структури світлом з енергією E = 1,12 еВ викликає різке зменшення т. При зростанні прикладеної до структури напруги т зменшується.